Paradigma Bahasa Pemrograman - Subandijo, Subandijo (Bina Nusantara University, 2011)
This article discusses several paradigms used in developing computer programs which is varied from the classical ? goto programming, until the modern one ? object oriented programming. In addition, the main features of each paradigm, the advantages and disadvantages of each paradigm and the comparation of procedural programming, the object oriented programming, and an additional feature like generic programming for the object oriented programming are also discussed in this article.